Development of solar oven incorporating thermal energy storage application - Firdaus, Muhamad (2012)
This project is about developed and fabricated a functional solar oven incorporating with thermal storage application. This report is to study the performance and characteristic of the oven using different parameter such as aluminum panel, aluminum wall inside the oven and thermal energy storage application. The structural three dimensional solid modeling of this oven was developed using the SOLIDWORK drawing software. The data were collected from four experiments which is used difference parameter for each experiment. Steel bar is used as a product to be measured to find the efficiency of the oven. Another temperatures parameter involved was an aluminum tray which is where the steel bar was placed during the experiment, oven temperature itself and river rock that used as thermal energy storage application. The comparisons of parameter’s temperature for each experiment were discussed in chapter 4 and the result shown that the thermal energy storage application was successful increase the oven efficiency.